2021
DOI: 10.1111/jocs.15756
|View full text |Cite
|
Sign up to set email alerts
|

Acute right ventricular failure in a patient with nonischemic cardiogenic shock on left‐sided mechanical circulatory support

Abstract: We report a case of acute right ventricular failure in a patient with cardiogenic shock on left-sided mechanical circulatory support with Impella 5.0. The patient was successfully bridged to heart transplantation using additional right-sided support with Protek Duo. Key learning points of the case include prompt recognition of acute right ventricular failure in patients on left-sided support, early consideration of right-ventricular mechanical support platforms, and timely deployment of rightsided mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Once the patient's hypoxia resolved, the ML was removed from the circuit, leaving the ProtekDuo® as a traditional percutaneous, temporary RVAD in a (dl)VxP configuration. The patient underwent heart transplantation and was discharged from the hospital [51].…”
Section: Protekduo® Cannula and Impella 50 And 55mentioning
confidence: 99%
“…Once the patient's hypoxia resolved, the ML was removed from the circuit, leaving the ProtekDuo® as a traditional percutaneous, temporary RVAD in a (dl)VxP configuration. The patient underwent heart transplantation and was discharged from the hospital [51].…”
Section: Protekduo® Cannula and Impella 50 And 55mentioning
confidence: 99%
“…Acute RV failure after LVAD implantation is reported to occur in up to 40% of cases [26,[41][42][43][44]. Multiple causes, either alone or in combination, including unmasking of chronic RV dysfunction once RV preload increases, distortion of RV geometry due to bowing of the intraventricular septum toward the LV due Perspective Chapter: The ProtekDuo® Cannula for Acute Mechanical Circulatory Support DOI: http://dx.doi.org/10.5772/intechopen.111537 to mechanical LV unloading, ventricular dysrhythmias, and embolic phenomenon to the coronary or pulmonary circulation are thought to precipitate RV failure [45]. Patients with LVADs who develop additional acute RV failure and require biventricular support have a high mortality [26].…”
Section: Protekduo® For Biventricular Failurementioning
confidence: 99%
“…Routh and coauthors reported a case of a 61-year old man with inotrope-dependent nonischemic cardiomyopathy who developed acute cardiogenic shock initially treated with Impella 5.5. The patient subsequently developed acute RV failure and a ProtekDuo® cannula was placed, allowing for biventricular support [45]. Ramamurthi et al reported a case series of six patients who underwent carotid placement of an Impella 5.5 for left ventricular support.…”
Section: Protekduo® With Temporary Lvadsmentioning
confidence: 99%